Let's play, Crabby! - Fenske, Jonathan (2019)
Crabby is a very grumpy crab, so Plankton tries to find a game that will cheer Crabby up, but Crabby does not want to play Simon says or hide-and-seek---will a game of tag be more to Crabby's taste?
4-6
Keywords: Crabs -- Juvenile fiction; Plankton -- Juvenile fiction; Games -- Juvenile fiction; Play -- Juvenile fiction; Humorous stories; Crabs -- Fiction; Plankton -- Fiction; Games -- Fiction; Play -- Fiction; Humorous stories; Humorous fiction; Picture books